Empowering junior high school dance education: a multimedia literacy-based competency approach for prospective teachers - Beben Barnas; Juju Masunah; Tati Narawati; Cepi Riyana (Gelar: Jurnal Seni Budaya, 2025)
This study develops interactive thematic dance teaching materials integrating multimedia literacy through a competency-based approach, addressing theoretical gaps in technology integration within arts education. The research adapts Majumdar's multimedia literacy model into a six-stage pedagogical framework for kinesthetic learning, empirically validating pre-service teachers' capacity as content creators. Using Research and Development with the Thiagarajan 4D model, 27 pre-service teachers designed interactive materials validated by three experts and field-tested with 30 junior high school students. Expert validation rated materials as "Suitable" (M=4.00/5.00). Regression analysis confirmed multimedia literacy awareness significantly predicted product creation ability (β=0.505, p=0.007). Field implementation showed high effectiveness: attractiveness 98.3%, learning skills 96.1%, and all indicators >88%. This framework advances arts education by demonstrating that disciplinary authenticity and technological innovation coexist synergistically, preserving aesthetic values while enhancing digital competencies for 21st-century learning.